THE STATE, FAMILY LAW AND WOMEN IN THE MIDDLE EASTERN AND NORTH AFRICAN REGION (MENA REGION): A COMPARATIVE SURVEY OF THE CURRENT REFORMS IN MOROCCO AND TUNISIA - Booley, Ashraf (Jurnal Syariah, 2019)
Islam and codification of its family law in countries such as Morocco and Tunisia have taken on a somewhat of a different character depending on the specific setting in which it took place. Even though Islamic thought and in general Islamic law contains core principles observed throughout the Islamic world. Most aspects of Islamic law relating to the family originate in the divine text, while others may be found in customs of certain communities situated in different parts of the Muslim world. Some of the early reforms enacted by states such as Morocco and Tunisia have been hailed as victories for the rights of women especially where Islam is the dominant religion in those countries. A historical and comparative analysis relating to the rights of women reveal that this was not always the case. It may be argued that women rights were ancillary to the main agenda of those respective countries. Issues such as modernity, breaking the shackles of kinsman, classism and political alliances were deemed to be high on the agenda of those countries. In Morocco and Tunisia, the state, early reformers and women’s activism played and continues to play an important role or perhaps an indirect role in securing women-friendly rights in the family. In other Muslim jurisdictions, Islamic law has been left intact or very little change has occurred. The argument in those states is that Islamic law cannot be changed or re-interpreted. In this paper we investigate the reforms which have taken place in each country and why these countries have been hailed as being sensitive to the issue of women’s rights. Although, these countries have been viewed as the vanguard of women friendly rights inequality does exist as new threats to the securing of women’s rights are on the horizon.